Ecological Economics: Themes, Approaches, and Differences with Environmental Economics - Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2000)
This provides a short overview of the main themes of ecological economics (EE). It isargued that EE provides a platform that fosters multidisciplinary environmental research bybringing together the core contributing disciplines economics and ecology. In addition, EE isregarded as a pluralistic approach to environmental research that can be set opposite to, and hasindeed developed as a response to, traditional environmental and resource economics. Acomparison of the two fields is presented to clarify the essential differences between them. Inaddition, specific themes are examined in more detail. These include: sustainable development;the growth debate; international trade; dynamic processes; and behaviour and policy.
Keywords: 330; Comparison; Environmental policy; Growth debate; Individual behaviour; International trade; Multilevel dynamics; Umweltökonomik; Theorie